ANALYSIS OF THE FACTORS CAUSING THE DECREASE OF ORGAN DONATION IN MALAYSIA - Rosli, Siti Nur Hidayah; Ahmad Tajudin, Amalina (SALAM Digest: Syariah and Law Undergraduate Symposium, 2024)
Organ donation has emerged as a critical issue in recent times, particularly due to the ongoing shortage of available organs. This shortage is largely attributed to the low percentage of individuals pledging to donate their organs. As a result, the insufficient number of organ donors leads to a significant shortage of organs for transplantation. Organ donation remains a vital and effective treatment method for patients suffering from end-stage organ failure. The demand for organ transplants has grown substantially, driven by the success of numerous transplants made possible by advancements in medical technology. However, a severe organ shortage could lead to more individuals being placed on transplant waiting lists, with many dying while awaiting a transplant. This study seeks to investigate the factors contributing to the decline in organ donation pledges. Additionally, it explores the significance of organ donation from an Islamic perspective and examines the relevant Fatwas in Malaysia. The study will also identify the different types of organ donors and propose potential solutions to address the underlying causes of this issue. The findings aim to provide insights into improving organ donation rates, offering recommendations for policies and strategies to promote organ donation in Malaysia.